2019
DOI: 10.1038/s41586-019-0985-x
|View full text |Cite
|
Sign up to set email alerts
|

NR4A transcription factors limit CAR T cell function in solid tumours

Abstract: Reprints and permissions information is available at www.nature.com/reprints.Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
548
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(602 citation statements)
references
References 46 publications
23
548
1
1
Order By: Relevance
“…However, higher expression levels of inhibitory receptors observed in the GFP hi population were not unique to SKGNur T cells since WTNur GFP hi CD4 T cells also upregulated inhibitory receptors compared to WTNur GFP lo CD4 T cells. This is in line with a recent report demonstrating that NR4A gene expression positively correlated with PDCD1 (PD-1), TIGIT, and other inhibitory receptors in the setting of chronic antigen stimulation as part of a T cell-intrinsic program of hyporesponsiveness (40). This may in part account for the relative hyporesponsiveness we observed in GFP hi T cells ( Fig.…”
Section: Upregulation Of Several Inhibitory Receptors In Skg Gfp Hi Csupporting
confidence: 93%
“…However, higher expression levels of inhibitory receptors observed in the GFP hi population were not unique to SKGNur T cells since WTNur GFP hi CD4 T cells also upregulated inhibitory receptors compared to WTNur GFP lo CD4 T cells. This is in line with a recent report demonstrating that NR4A gene expression positively correlated with PDCD1 (PD-1), TIGIT, and other inhibitory receptors in the setting of chronic antigen stimulation as part of a T cell-intrinsic program of hyporesponsiveness (40). This may in part account for the relative hyporesponsiveness we observed in GFP hi T cells ( Fig.…”
Section: Upregulation Of Several Inhibitory Receptors In Skg Gfp Hi Csupporting
confidence: 93%
“…Recent studies have identified TOX, TOX2, and AP-1 family members as central regulators of human T cell exhaustion that promote widespread transcriptional and epigenetic dysregulation (Alfei et al, 2019;Khan et al, 2019;Scott et al, 2019;Seo et al, 2019;Wang et al, 2019;Yao et al, 2019). These findings have enabled new approaches to mitigate exhaustion, including enforced expression of c-Jun or CRISPR-mediated deletion of TOX, TOX2, or NR4A family TFs (Chen et al, 2019a;Seo et al, 2019). However, such modifications do not result in wholescale remodeling of the exhaustion-associated epigenome, suggesting that exhaustion is an epigenetically fixed cell state.…”
Section: Discussionmentioning
confidence: 99%
“…158,159 This raises the possibility that Nr4a family members collectively may play additional undiscovered roles in B cell tolerance. Indeed, recent work shows that the Nr4a family plays a role in down-modulating T cell responses to chronic antigen stimulation by engaging the exhaustion program in CD8 T cells and the "anergy program" in CD4 T cells that receive signal one without co-stimulation.…”
Section: Con Clus I On S and Future Direc Tionsmentioning
confidence: 99%
“…Indeed, recent work shows that the Nr4a family plays a role in down-modulating T cell responses to chronic antigen stimulation by engaging the exhaustion program in CD8 T cells and the "anergy program" in CD4 T cells that receive signal one without co-stimulation. 158,159 This raises the possibility that Nr4a family members collectively may play additional undiscovered roles in B cell tolerance. To unmask redundancy among this three-member family, conditional elimination of multiple family members will be necessary.…”
Section: Con Clus I On S and Future Direc Tionsmentioning
confidence: 99%